PENGARUH KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA DIMEDIASI OLEH MOTIVASI KERJA PADA PEGAWAI DINAS PENDIDIKAN KABUPATEN KERINCI - Mutiya Fadliana; Zefriyenni; Yulasmi (Journal Publicuho, 2025)
This study aims to examine the effect of job satisfaction and discipline on performance mediated by work motivation. A quantitative approach with hypothesis testing techniques was used in this study. There were 98 samples with the saturated sample technique, namely, all employees in the Education Office of Kerinci Regency, Jambi. Data were collected through distributing questionnaires online and processed using SmartPLS 4.0 software with structural equation modelling techniques. The results showed that job satisfaction and work discipline each had a positive and significant effect on work motivation. Job satisfaction and work discipline each have a positive and significant effect on performance, but not significant by work motivation. Work motivation is not able to mediate the relationship between job satisfaction and performance,e and work discipline and performance. The implications of the research emphasise the importance of maintaining the morale and integrity of employees in government agencies in order to produce good-quality work.